Accessibility and Usability of Selected Information Systems in Ghana with focus on Foreigners - Adu, Daniel (Univerzita Pardubice, 2019)
The aim of this paper is to propose a suitable procedure of accessibility and usability evaluation of selected information systems in Ghana for foreigners. Selected everyday designated life situations will be used as a base for evaluation. List of recommendations on how to improve evaluated information systems will represent another output of the thesis. SortSite evaluation tool was used in the evaluation process. It is an automated software which can be used to evaluate both usability and accessibility of a website. The findings of the thesis show that the government of Ghana needs to implement laws which will enforce the designers to comply with rules and regulation governing web creation.
Přístupnost a použitelnost vybraných informačních systémů zaměřených na cizince v Ghaně
Keywords: informační systémy; přístupnost; použitelnost; Ghana; cizinci; information systems; accessibility; usability; Ghana; foreigners